A study on fishery management of Bergobindapur baor at Chaugachha upazila under Jessore district, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was conducted on Bergobindapur baor at Chaugachha upazila under Jessore district. The study period was February to June, 2015. Data were collected by using participatory rural appraisal (PRA) tools and personal observation. Stocking densities of silver carp, catla, rohu, mrigal, grass carp, common carp (size 5-6 inch) were 48, 15, 35, 28, 16 and 10 kg/ha and composition were 31%, 10%, 23%, 19%, 10% and 7% in the fiscal year 2013-2014, respectively. In 2014-2015 stocking densities of silver carp, catla, rohu, mrigal, grass carp, common carp (size 5-6 inch) were 28, 9, 23, 9, 9 and 14 kg/ha and composition were 30%, 10%, 25%, 10%, 10%, and 15%, respectively. Total stocking density of carp species was 152 kg/ha in the fiscal year 2013-2014 and 92 kg/ha in 2014-2015. Production of carps and SIS were 345.62 and 258.065 kg/ha in 2013-2014 and 323.065 and 276.50 kg/ha in 2014-2015, respectively. In the study area, seine net was used for komor and kochal (local name) fishing. Carp species harvested by komor and kochal fishing in 2013-2014 were 276.50 kg/ha, 69.12 kg/ha and in 2014-2015 were 274.61 and 48.43 kg/ha, respectively. Marketing channel started from the fishermen and carp fishes were supplied to three markets namely Chaugachha, Jessore and Jhenidah. The findings of this  study assumed that production of fish could be increased 25% through an effective management practices.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 291-296